ANALISIS TINGKAT KENYAMANAN TERMIS DI WILAYAH KOTA TANGERANG BERDASARKAN TEMPERATURE HUMIDITY INDEX - Dyah Ajeng Sekar Pertiwi; Jaka Anugrah Ivanda Paski (Jurnal Manajemen Bencana (JMB), 2021)
Hydrometeorological disasters are not always associated with an extreme event, climate change, and the geographical location of an area have an impact on physiological comfort in residential areas. In addition, the rapid development of an area also has an impact on weather parameters that affect the level of comfort. This research was conducted to determine the comfort level in Tangerang City using THI (Temperature Humidity Index) analysis of the parameters of air temperature and humidity. The value of the comfort level is divided using a comfort interval, for THI values between 21-24 °C there are 100% of the population declaring comfortable, THI between 25-27 °C only 50% of the population feels partially comfortable, and THI> 27 °C as much as 100% the population feels uncomfortable. Based on climate data from 1986-2009 at Soekarno-Hatta Meteorological Station of Cengkareng, the results showed an average percentage of daily comfort levels with a comfortable category of 9,5% (35 days per year), some comfortable 79,2% (289 days per year) and uncomfortable 11,3% (41 days per year). During this period, there was an increase in the THI index in Tangerang City which tended to be increasingly uncomfortable.